Organic carbon pools in an Oxisol cultivated with vegetables under different managements - Lima, Carlos Eduardo Pacheco; Fontenelle, Mariana Rodrigues; Madeira, Nuno Rodrigo; Silva, Juscimar da; Guedes, Ítalo Moraes Rocha; Silva, Luciana Rodrigues Borba; Soares, Daiane Costa (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the contents of total organic carbon (COT) and of the organic matter fractions in an Oxisol cultivated with vegetables under different soil management systems and with different cover crops. The experiment was carried out for six years in a randomized block design, in a 3x2 factorial arrangement with three soil management systems – no-tillage (SPD), minimum tillage (PPR), and conventional system (SPC) –, and two cover crops, one of maize and the other of maize intercropped with Stizolobium niveum (MM), with four replicates. COT levels, estimated for 0.00–0.30-m, soil depth were higher in SPD and PPR. Regardless of the evaluated soil depth, MM intercropped system promoted higher contents of particulate organic carbon (COP), which were strongly affected by straw incorporation. In all soil depths, negative correlations were observed between the contents of COP and those of carbon associated to minerals (COAM), which indicate the occurrence of priming effect. COT contents were positively correlated to those of COAM, stressing the importance of soil organic matter stabilization mechanisms for improving COT contents in the soil.